2020
DOI: 10.1177/2055116920972077
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal cutaneous non-epitheliotropic B-cell lymphoma in a cat

Abstract: Case summary Skin tumours are the second-most common form of feline cancer after haematopoietic neoplasms and are often malignant. Cutaneous lymphoma is uncommon in cats and can be classified as epitheliotropic (typically of T-cell origin) or non-epitheliotropic (either of T-cell or B-cell origin). The present study describes a case of multifocal cutaneous non-epitheliotropic B-cell lymphoma. The skin nodules were multiple and variable in size; showed rapid progression; were alopecic and erythematous in appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The epitheliotropic and non-epitheliotropic forms can have similar clinical appearances. The lesions may be solitary or diffuse and are often described by various manifestations such as erythematous spots, alopecia, scales, skin nodules, or ulcerative plaques [5,7]. The period of existence of the lesion before diagnosis varies from case to case: the lesions can last up to 2 years in NECL [10], and the lesion progressed rapidly and worsened within 2 months in this case.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…The epitheliotropic and non-epitheliotropic forms can have similar clinical appearances. The lesions may be solitary or diffuse and are often described by various manifestations such as erythematous spots, alopecia, scales, skin nodules, or ulcerative plaques [5,7]. The period of existence of the lesion before diagnosis varies from case to case: the lesions can last up to 2 years in NECL [10], and the lesion progressed rapidly and worsened within 2 months in this case.…”
mentioning
confidence: 85%
“…Most epitheliotropic tumors are of T-cell origin, and the tumor cells infiltrate the epidermis and adnexal epithelium in ECL [3]; however, tumor cells are of either T-cell or B-cell origin and do not usually involve the adnexal gland in NECL [4]. Previous studies have reported that the prognosis of NECL is grave, and its median survival time appears to be shorter than that of ECL [3,5]. Herein, we report a case to describe clinical and pathological findings of T-cell NECL in a cat.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…11 Primary cutaneous lymphomas account for 0.2%-3% of all feline lymphomas, with nonepitheliotropic lymphomas reported more frequently than epitheliotropic forms. [12][13][14] Primary nonepitheliotropic cutaneous lymphomas reported in cats comprise indolent T-cell lymphoma, also referred to as cutaneous lymphocytosis, 15 multifocal cutaneous B-cell lymphoma, 16 T-cell-rich B-cell lymphoma, 12,17 and injection site lymphoma. 18 Thus, because of the lack of documentation, we believe that this study represents the first documentation of SPTCL in cats presenting features that resemble the human and canine forms of the disease.…”
Section: O R I G I N a L A R T I C L E Subcutaneous Panniculitis-like...mentioning
confidence: 99%